Impact of advanced cloud microphysics schemes for the Kerala flood events in 2018 and 2019 using the NCMRWF regional model - Rose Raphel; A. Jayakumar; T.J. Anurose; Saji Mohandas; Greeshma M. Mohan; M. Sandhya; Anumeha Dube; Donali Gogoi; V.S. Prasad; Claudio Sanchez (Atmospheric Research, 2026)

ARF Gene Family: Expression Dynamics, Signalling, and Importance in Seed Development - Kumari Arpita; Sandhya Sharma; Anshika Tyagi; Arvind Yadav; Sandeep Kumar; Rupesh Deshmukh; Robert M Stupar; Kishor Gaikwad (Journal of Plant Growth Regulation, 2026)

Improving lightning representation in global model through convective cloud based Price and Rind 1992 scheme - M. Sandhya; Greeshma M. Mohan; Saji Mohandas; A. Jayakumar; T.J. Anurose; V.S. Prasad (Science of The Total Environment, 2026)

Plasma pTau181 is associated with subjective cognitive concerns but not objective cognitive decline or structural brain integrity measures in midlife - Ashleigh Barrett-Young; Erin E. Cawston; Brigid Ryan; Wickliffe C. Abraham; Antony Ambler; Tim Anderson; Kirsten Cheyne; Elizabeth Goodin; Sean Hogan; Renate M. Houts; David Ireland; Annchen R. Knodt; et al. (GeroScience, 2026)
Although plasma pTau181 has been shown to accurately discriminate patients with Alzheimer’s disease from healthy older adults, there are few studies of plasma biomarkers among middle-aged populations. Given the potential utility of plasma AD biomarkers such as pTau181 in screening for disease risk, examining pTau181 in a middle-aged cohort without AD is important for future implementation. The objectives of this study were to characterise plasma pTau181 in a middle-aged birth cohort aged 45 years and to investigate associations with early indicators of dementia risk. Participants were members of the Dunedin Multidisciplinary Health and Development Study, a longitudinal study of 1037 people born in New Zealand in 1972–1973. Plasma pTau181, self-reported cognitive concerns, MRI-based brain structure, and DunedinPACE (an epigenetic biomarker of biological ageing) were measured at age 45; cognition was measured in childhood and age 45. Plasma pTau181 concentrations at age 45 ( n = 854, 49% female) were associated with self-reported cognitive concerns (β = 0.09, p = .008); however, no significant associations were observed with objective cognitive decline, worse structural brain integrity, or biological ageing. Higher plasma pTau181 was associated with self-reported cognitive concerns at age 45, but not objective AD-related measures. The association of plasma pTau181 and self-reported cognitive concerns in this cohort suggests that AD pathology may begin to accumulate by age 45 and may be associated with subtle changes in cognition that are not at objectively measurable levels. Graphical Abstract

Fungal Foe Unveiled: AlphaFold-based 3D structure prediction of Rhizopus delemar 1,3-β-Glucan synthase and virtual screening for the identification of potential inhibitors - Sandhya Kushwaha; Deevena Kumari; Sonia Kumari; M. Elizabeth Sobhia (In Silico Pharmacology, 2026)

Cultural, pathogenic and genetic variability of Rhizoctonia solani isolates incitant of rice sheath blight disease - Y. Sandhya; M. Reddi Kumar; P. Madhusudhan; P. Sudhakar; P. Lavanya Kumari (Vegetos, 2026)

First report of the fiery box jellyfish Morbakka virulenta (Kishinouye, 1910) in Indian waters identified through integrative taxonomy - Ajay Kumar Jena; R. Amal; S.V. Sandhya; M. Aparna; Biraja Kumar Sahu (Regional Studies in Marine Science, 2026)

Application of otolith morphology to unveil the stock structure of Hilsa shad (Tenualosa ilisha) in the Bhagirathi-Hooghly river system and the associated Northern Bay of Bengal - Sajina A.M.; Sangeetha M. Nair; Suresh V.V.R.; T. Maity; J. Mukherjee; S.K. Banik; Sandhya K.M.; R.K. Manna; R. Samanta (Regional Studies in Marine Science, 2025)

Enhanced Delivery of Methotrexate for Scalp Psoriasis Treatment via Nanosuspension Hair Dye: A Box-Behnken Optimization Approach - Poojitha P.N.; Akhil Perumalla; Sandhya Rachamalla; shirisha Mandli; Shilpa Ajje; Sindura Talari; Shaik Afroz Kottapalli; Nagashubha B; M. Kiran Sai (Journal of Pharmaceutical Innovation, 2025)

Effect of explant sources, sonication combined with vacuum infiltration, and biochar on improving Agrobacterium-mediated transformation efficiency in Eucalyptus camaldulensis - M. C. Sandhya; Sreeja Sahadevan; Krishnaraj Shamili; Manoj Kumar Rajendran; Harshita Singh; Aiyar Balasubramanian; Muthukrishnan Arun; Sivakumar Veerasamy; Mathish Nambiar-Veetil (Plant Biotechnology Reports, 2025)

LP-53 Evaluation of the Mutagenic Potential of 1-Cyclopentyl-4-Nitrosopiperazine Nitrosamine in Human Lymphoblastoid TK6and CHO-K1 Cells - M. Shameer P; T. Pradeep; M. Rajini; A. Mariappan; S. Sandhya; G. Kulavardhan; M. Sumithra; R. Harika; A. Varun; K. Mohan; V. Deepa (Toxicology Letters, 2025)

Healing power of Neltuma juliflora (Sw.) Raf.: a comprehensive review of its phytochemicals, pharmacology aspects, and potential health benefits - S. Deepthi; K. Narsimha; K. Ashwini; M. Sandhya Rani; K. Suresh Babu (Natural Product Research, 2025)

On the role of Sri Lankan land mass in safeguarding the southeastern coast of India from Southern Ocean swell attacks - K G Sandhya; R Harikumar; P A Francis; Balaji Baduru; T M Balakrishnan Nair (Journal of Earth System Science, 2025)

First report of Curvularia lunata as causal agent of Curvularia blight in potato and tomato crops in Mauritius - Nooreen Mamode Ally; Sandhya D. Takooree; Vijayanti M. Ranghoo-Sanmukhiya; Hudaa Neetoo (Indian Phytopathology, 2025)

A hybrid approach: remote sensing, analytic hierarchy process and geographic information system for groundwater potential mapping in Dediapada, India - Garge Sandhya Kiran; Ramandeep Kaur M. Malhi; Agradeep Mohanta (Environmental Science and Pollution Research, 2024)

A paradigm assessment of low-cost ceramic membranes: Raw materials, fabrication techniques, cost analysis, environment impact, wastewater treatment, fouling, and future prospects - K.V.V. Satyannarayana; Randeep Singh; S. Lakshmi Sandhya Rani; M. Sreekanth; Vinoth Kumar Raja; Young-Ho Ahn (Journal of Water Process Engineering, 2024)

Cryo-conservation of temperate berry crops at ICAR-NBPGR - Sandhya Gupta; Narender Negi; Sheikh M. Sultan (Cryobiology, 2024)

Silver nanoparticle-induced in vitro flowering in Dendrocalamus strictus (Roxb.) nees and genetic fidelity assessment of regenerants using molecular markers - Bharat Singh Rajput; M. Manokari; Nitin J. Solanki; Dulam Sandhya; Mohammad Faisal; Abdulrahman A. Alatar; Mahipal S. Shekhawat (Molecular Biology Reports, 2024)

Acute Administration of HIV-1 Tat Protein Drives Glutamatergic Alterations in a Rodent Model of HIV-Associated Neurocognitive Disorders - Brenna C. Duffy; Kirsten M. King; Binod Nepal; Michael R. Nonnemacher; Sandhya Kortagere (Molecular Neurobiology, 2024)
HIV-1-associated neurocognitive disorders (HAND) are a major comorbidity of HIV-1 infection, marked by impairment of executive function varying in severity. HAND affects nearly half of people living with HIV (PLWH), with mild forms predominating since the use of anti-retroviral therapies (ART). The HIV-1 transactivator of transcription (Tat) protein is found in the cerebrospinal fluid of patients adherent to ART, and its administration or expression in animals causes cognitive symptoms. Studies of Tat interaction with the N -methyl- D -aspartate receptor (NMDAR) suggest that glutamate toxicity contributes to Tat-induced impairments. To identify changes in regional glutamatergic circuitry underlying cognitive impairment, we injected recombinant Tat86 or saline to medial prefrontal cortex (mPFC) of male Sprague–Dawley rats. Rats were assessed with behavioral tasks that involve intact functioning of mPFC including the novel object recognition (NOR), spatial object recognition (SOR), and temporal order (TO) tasks at 1 and 2 postoperative weeks. Following testing, mPFC tissue was collected and analyzed by RT-PCR. Results showed Tat86 in mPFC-induced impairment in SOR, and upregulation of Grin1 and Grin2a transcripts. To further understand the mechanism of Tat toxicity, we assessed the effects of full-length Tat101 on gene expression in mPFC by RNA sequencing. The results of RNAseq suggest that glutamatergic effects of Tat86 are maintained with Tat101, as Grin2a was upregulated in Tat101-injected tissue, among other differentially expressed genes. Spatial learning and memory impairment and Grin2a upregulation suggest that exposure to Tat protein drives adaptation in mPFC, altering the function of circuitry supporting spatial learning and memory.

Industrial symbiosis and eco-industrial transformation opportunities for environmental protection in Nigeria - Abubakar M. Bilyaminu; Eldon R. Rene; Ashok Pandey; Sandhya Babel; Quinnetta Blessing Clement; Anina James; Hector Garcia Hernandez (Sustainable Production and Consumption, 2024)

An in vitro model of adipose tissue-associated macrophages - Karishma Bhatia; Sandhya Tiwari; Vikas Kumar Gupta; Neerav M Sapariya; Sanjeev K Upadhyay (Journal of Biosciences, 2024)

Monitoring genetic transformation with RUBY visible reporter in Nicotiana tabaccum L. - Phanikanth Jogam; Vaishnavi Anumula; Dulam Sandhya; M. Manokari; Ajay Kumar Venkatapuram; V. Mohan Murali Achary; Mahipal S. Shekhawat; Venkataiah Peddaboina; Venkateswar Rao Allini (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Hydrogen and biodiesel production from food waste: a review - Julkipli Julkipli; Sandhya Babel; Abubakar M. Bilyaminu; Eldon R. Rene (Environmental Chemistry Letters, 2024)

Spectral mixture analysis of AVIRIS-NG data for grouping plant functional types - Ramandeep Kaur M. Malhi; G. Sandhya Kiran; Prashant K. Srivastava; Bimal K. Bhattacharya; Agradeep Mohanta (Advances in Space Research, 2024)

Efficient extraction and analysis of precious metals with a conducting polymer modified magnetic sorbent material - Abiral Poudel; Sandhya Adhikari; Timnit Y. Asfaha; Joseph G. Lawrence; Manjula M. Kandage; Michal Marszewski; Jon R. Kirchhoff (Resources, Conservation and Recycling, 2023)

High doses of clethodim-based herbicide GrassOut Max poses reproductive hazard by affecting male reproductive function and early embryogenesis in Swiss albino mice - Reyon Dcunha; Sandhya Kumari; Mohd Altaf Najar; Anjana Aravind; Keerthana Sandesh Suvarna; Ananda Hanumappa; Sadhana P. Mutalik; Srinivas Mutalik; Sneha Guruprasad Kalthur; G.K. Rajanikant; Sazada Siddiqui; Sulaiman Alrumman; et al. (Chemosphere, 2023)

On drastic change in the relationship between snow cover and Indian monsoon rainfall - M Sandhya; S Sridharan (Journal of Earth System Science, 2023)

Edible oil to powder technologies: Concepts and advances - K. Sandhya; M. Maria Leena; J.A. Moses; C. Anandharamakrishnan (Food Bioscience, 2023)

Recent advances in Surface Plasmon Resonance (SPR) biosensors for food analysis: a review - Nevetha Ravindran; Sandhya Kumar; Yashini M; Rajeshwari S; Mamathi C A; Nirmal Thirunavookarasu S; Sunil C K (Critical Reviews in Food Science and Nutrition, 2023)

Defect-induced electronic modification and surface reconstruction of catalysts during water oxidation process - Gracita M. Tomboc; Sandhya Venkateshalu; Quang-Tung Ngo; Songa Choi; Bruno G. Pollet; Hangil Lee; Kwangyeol Lee (Chemical Engineering Journal, 2023)

Population genetic research on the Spadenose shark, Scoliodon laticaudus (Chondrichthyes, Carcharhinidae), reveals the presence of two significantly differentiated clades along the Indian coast - Sandhya Sukumaran; Wilson Sebastian; P. U. Zacharia; Shoba J. Kizhakudan; K. V. Akhilesh; Sujitha Thomas; Subal Kumar Roul; M. Muktha; Swati Priyanka Sen; G. B. Purushottama; Shikha Rahangdale; K. K. Bineesh; et al. (Marine Biodiversity, 2023)

Exome sequencing and microarray identified a novel large exonic deletion in SYT2 gene in an ultra-rare case with recessive CMS type 7 - C. P. Ravi Kumar; Parag M. Tamhankar; Radhika Manohar; Sheetal Sharda; G. K. Madhavilatha; S. G. Thenral; Sandhya Nair; A. K. Bojamma (Journal of Genetics, 2022)

Influence of southern hemispheric upper troposphere potential vorticity intrusion events on the southwest monsoon rainfall - M Sandhya; S Sridharan (Journal of Earth System Science, 2022)

Development of marker-free insect resistant transgenic okra (Abelmoschus esculentus L. Moench) expressing the cry1Ac gene and identification of vector backbone-free events - Satish Deole; Sanjeev Padakipatil; S. R. Sandhya; Asaram Nanote; Murlidhar Jadhav; Pankaj Bihani; Srinivas Parimi; Usha Zehr; M. Narendran; Bharat R. Char (Physiology and Molecular Biology of Plants, 2021)

Status of Hilsa Fishery in Hooghly-Bhagirathi River System and Associated Coastal Waters of Northern Bay of Bengal - A. M. Sajina; V. R. Suresh; K. M. Sandhya; J. Mukherjee; R. K. Manna; B. K. Behera; R. Samanta; T. Maity; S. K. Banik (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

Synergetic use of in situ and hyperspectral data for mapping species diversity and above ground biomass in Shoolpaneshwar Wildlife Sanctuary, Gujarat - Ramandeep Kaur M. Malhi; Akash Anand; Ashwini N. Mudaliar; Prem C. Pandey; Prashant K. Srivastava; G. Sandhya Kiran (Tropical Ecology, 2020)

Development and Investigation of Vitamin C-Enriched Adapalene-Loaded Transfersome Gel: a Collegial Approach for the Treatment of Acne Vulgaris - Sandhya Vasanth; Akhilesh Dubey; Ravi G.S.; Shaila A. Lewis; Vivek M. Ghate; Sally A. El-Zahaby; Srinivas Hebbar (AAPS PharmSciTech, 2020)

Isolation and phylogenetic identification of heterotrophic thraustochytrids from mangrove habitats along the southwest coast of India and prospecting their PUFA accumulation - K. V. Jaseera; P. Kaladharan; K. K. Vijayan; S. V. Sandhya; M. Leo Antony; M. A. Pradeep (Journal of Applied Phycology, 2019)

Spectral Modelling on the Characteristics of High Frequency Tail in Shallow Water Wave Spectra at Coastal Puducherry, East Coast of India - P. A. Umesh; Prasad K. Bhaskaran; K. G. Sandhya; T. M. Balakrishnan Nair (Pure and Applied Geophysics, 2019)

High Frequency Tail Characteristics in the Coastal Waters off Gopalpur, Northwest Bay of Bengal: A Nearshore Modelling Study - P. A. Umesh; Prasad K. Bhaskaran; K. G. Sandhya; T. M. Balakrishnan Nair (Pure and Applied Geophysics, 2018)

Re-description of the longtail butterfly ray, Gymnura poecilura (Shaw, 1804) (Gymnuridae: Myliobatiformes) from Bay of Bengal with a neotype designation - M. Muktha; K. V. Akhilesh; S. Sandhya; F. Jasmin; M. A. Jishnudev; Shoba Joe Kizhakudan (Marine Biodiversity, 2018)

Status, Prospects, Threats, and the Way Forward for Sustainable Management and Enhancement of the Tropical Indian Reservoir Fisheries: An Overview - U. K. Sarkar; K. M. Sandhya; P. Mishal; G. Karnatak; S. Kumari; P. Panikkar; R. Palaniswamy; M. Karthikeyan; S. Sibina Mol; T. T. Paul; V. L. Ramya; D. S. K. Rao; et al. (Reviews in Fisheries Science & Aquaculture, 2018)

Platform model describing pharmacokinetic properties of vc-MMAE antibody–drug conjugates - Matts Kågedal; Leonid Gibiansky; Jian Xu; Xin Wang; Divya Samineni; Shang-Chiung Chen; Dan Lu; Priya Agarwal; Bei Wang; Ola Saad; Neelima Koppada; Bernard M. Fine; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2017)

Fluorescence Quenching Property of C-Phycocyanin from Spirulina platensis and its Binding Efficacy with Viable Cell Components - Meenakshi B. Paswan; Meghna M. Chudasama; Madhusree Mitra; Khushbu Bhayani; Basil George; Shruti Chatterjee; Sandhya Mishra (Journal of Fluorescence, 2016)

Analysis of SARAL/AltiKa Wind and Wave over Indian Ocean and its Real-time Application in Wave Forecasting System at ISRO - Suchandra Aich Bhowmick; Ruchi Modi; K. G. Sandhya; M. Seemanth; T. M. Balakrishnan Nair; Raj Kumar; Rashmi Sharma (Marine Geodesy, 2015)

Development of a new CMS system in pigeonpea utilizing crosses with Cajanus lanceolatus (WV Fitgz) van der Maesen - Sandhya Srikanth; Rachit K. Saxena; M. V. Rao; Rajeev K. Varshney; Nalini Mallikarjuna (Euphytica, 2015)

Semi-mechanistic Multiple-Analyte Pharmacokinetic Model for an Antibody-Drug-Conjugate in Cynomolgus Monkeys - Dan Lu; Jin Yan Jin; Sandhya Girish; Priya Agarwal; Dongwei Li; Saileta Prabhu; Randall C. Dere; Ola M. Saad; Denise Nazzal; Neelima Koppada; Saroja Ramanujan; Chee M. Ng (Pharmaceutical Research, 2015)

Production of polyhydroxyalkanoates from Ralstonia eutropha using paddy straw as cheap substrate - M. Sandhya; J. Aravind; P. Kanmani (International Journal of Environmental Science and Technology, 2013)

Contribution of GPR30 for 1,25 dihydroxyvitamin D3 protection in EAE - Sandhya Subramanian; Lisa M. Miller; Marjorie R. Grafe; Arthur A. Vandenbark; Halina Offner (Metabolic Brain Disease, 2012)

Vertical structure of sea-breeze circulation over Thumba (8.5°N, 76.9°E, India) in the winter months and a case study during W-ICARB field experiment - T. J. Anurose; D. Bala Subrahamanyam; C. B. S. Dutt; N. V. P. Kiran Kumar; Sherine Rachel John; Sandhya K. Nair; M. Santosh; Mannil Mohan; P. K. Kunhikrishnan; S. Sijikumar; S. S. Prijith (Meteorology and Atmospheric Physics, 2012)

Isotopic labeling of the heme cofactor in cytochrome p450 and other heme proteins - David Bryson; Pek-Lang Lim; Alin Lawson; Sandhya Manjunath; Gregory M. Raner (Biotechnology Letters, 2011)

Sustained expression of circulating human alpha-1 antitrypsin reduces inflammation, increases CD4+FoxP3+ Treg cell population and prevents signs of experimental autoimmune encephalomyelitis in mice - Sandhya Subramanian; Galit Shahaf; Eyal Ozeri; Lisa M. Miller; Arthur A. Vandenbark; Eli C. Lewis; Halina Offner (Metabolic Brain Disease, 2011)

Antioxidant and anti-stress compounds improve regrowth of cryopreserved Rubus shoot tips - Esther E. Uchendu; Magfrat Muminova; Sandhya Gupta; Barbara M. Reed (In Vitro Cellular & Developmental Biology - Plant, 2010)

Agrobacterium-Mediated Transformation of cry1Ac Gene into Shoot-Tip Meristem of Diploid Cotton Gossypium arboreum cv. RG8 and Regeneration of Transgenic Plants - S. B. Nandeshwar; Sandhya Moghe; P. K. Chakrabarty; M. K. Deshattiwar; Keshav Kranthi; P. Anandkumar; C. D. Mayee; B. M. Khadi (Plant Molecular Biology Reporter, 2009)

Forest change detection in Kalarani round, Vadodara, Gujarat— a Remote Sensing and GIS approach - Jessica P Karia; M C Porwal; P S Roy; G Sandhya (Journal of the Indian Society of Remote Sensing, 2001)

Elucidation of the lesions present in the transcription defectivefitA76 mutant ofEscherichia coli: Implication of phenylalanyl tRNA synthetase subunits as transcription factors - Sandhya Ramalingam; M. Hussain Munavar; S. Sudha; A. Ruckmani; R. Jayaraman (Journal of Biosciences, 1999)

Expression of hup Genes in Azorhizobium caulinodans and Their Coregulation With RuBP Carboxylase - Sandhya Sanghi; M. L. Lodha (Journal of Plant Biochemistry and Biotechnology, 1998)